Improving the luminescence performance of far-red-emitting Sr2ScSbO6:Mn4+ phosphor with charge compensation and its application in plant growth LEDs. (1st May 2023) - Xia, Weixi; Cheng, Hang; Mao, Qinan; Ding, Yang; Pei, Lang; Zhu, Yiwen; Liu, Meijiao; Wang, Chunhua; Zhong, Jiasong
Abstract: Mn 4+ activated oxide phosphor as plant growth LEDs is becoming a research hotspot owing to the high coincidence of spin-forbidden transition emission peaks in 2 Eg - 4 A2g with the photosensitive pigment Pfr required for plant growth. Moreover, the emission peaks of Mn 4+ can be adjusted at 610–750 nm depending on the matrix. However, Mn 4+ doped phosphors suffer from sharply decreased emission intensity at high temperature. In order to exploit phosphors with good thermal stability and high emission intensity, the charge compensation of the double perovskite structured phosphor Sr2 ScSbO6 :Mn 4+ using Li + dopant is conducted in this study, wherein the Li + doping inhibits the adverse energy transfer between Mn 4+, therefore increasing the luminescence intensity by 2.27 times and upgrading the thermal stability from 80.2% to 86.76% at 423 K with respect to its value at 303 K in comparison with that of pristine Sr2 ScSbO6 :Mn 4+ . Accordingly, an innovative PDMS-LED device is fabricated using the modified phosphor. The typical 2 Eg - 4 A2g emission peak of Mn 4+ at 697 nm under 365 nm UV chip excitation coincided well with the far-red light photosensitive pigment Pfr required for plant growth. Meanwhile, the thermal imaging tests demonstrate the outstanding working stability of the constructed PDMS-LED device at different temperatures. The above results indicate that the Sr2 ScSbO6 :Mn 4+ /Li + phosphor-based PDMS-LED device possesses high potential in promoting plant growth. Graphical abstract: Image 1